(untitled) (The Pretoria Student Law Review, 2021)
The European colonial invasion that birthed apartheid rule resulted in black women being the most vulnerable group to land dispossession.1 This vulnerability has been exacerbated by the ineffective measures of the law that, in an attempt to redress these past injustices, fail to afford adequate recognition to the racial, gender and socio-economic marginalisation of black women in the regulation of land issues.2 This essay essentially aims to highlight the intersectionality between the oppressions of gender, racial and class based discrimination, which black women in South Africa are afflicted by in relation to land ownership and the security of land tenure. This essay further illuminates how there is a crucial necessity for the decolonisation of the South African property law system as a whole, in order to address the problem of black women being the most vulnerable group to land dispossession in this democratic era. This evaluation is conducted by providing a critique of the Extension of Security of Tenure Act 62 of 1997 (‘ESTA’) in light of the Critical Race Feminist theory and with reference to various South African case law, in order to expose how issues of race, gender and class intersect within the context of land dispossession. Moreover, the essay progresses to explain the manner in which the interpretation of the South African property laws such as ESTA, positively transform legal knowledge. It should be noted that the legal transformation is not enough to address a dispossession of land from black women. Consequently, this essay argues that what is necessary in a South African context is the entire decolonisation of the property law system, which can serve as the appropriate measure for remedying the vulnerability of black women to land dispossession in this post1994 era.